The Hybrid Professional: Essential Digital and AI Skills for Health Jobs in 2025 - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The healthcare landscape is undergoing a profound transformation, driven by the rapid integration of digital technologies and artificial intelligence AI. Thi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics